2020
DOI: 10.1634/theoncologist.2019-0729
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Receptor–Positive/Human Epidermal Growth Receptor 2–Negative Metastatic Breast Cancer in Young Women: Emerging Data in the Era of Molecularly Targeted Agents

Abstract: Breast cancer is the most common malignancy in young women worldwide, accounting for an estimated 30% of new cancer diagnoses and 25% of cancer deaths. Approximately two thirds of young women with breast cancer have hormone receptor–positive (HR+)/human epidermal growth receptor 2–negative (HER2−) tumors. Numerous studies, primarily in early‐stage breast cancer, have demonstrated that young age is an independent risk factor for more aggressive disease and worse outcomes. Although more limited data are availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…Among luminal BCs, approximately 80% are ER-positive (estrogen-receptor positive), and about 65% of these are also PR-positive (progesterone-receptor positive) [10]. Luminal A cancers ER/PR-positive and HER-2 negative grow slowly in response to hormone stimulation and so can likely respond to hormone therapy, generally having the best prognosis [11]. Luminal B cancers occur with a quicker growth than luminal A, and their prognosis is slightly worse.…”
Section: Breast Cancer Clinical Classificationmentioning
confidence: 99%
“…Among luminal BCs, approximately 80% are ER-positive (estrogen-receptor positive), and about 65% of these are also PR-positive (progesterone-receptor positive) [10]. Luminal A cancers ER/PR-positive and HER-2 negative grow slowly in response to hormone stimulation and so can likely respond to hormone therapy, generally having the best prognosis [11]. Luminal B cancers occur with a quicker growth than luminal A, and their prognosis is slightly worse.…”
Section: Breast Cancer Clinical Classificationmentioning
confidence: 99%
“…We also reviewed study which reported that HER2 did not have an prognostic in uence on HR-positive young BC [27]. Age has been de ned as an independent risk factor for survival in BC patients [9,28,29]. Xu et al reported a 95.2% 5-year OS in patients under age 60 (mainly composed of post-menopausal women ) [30].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a higher proportion of endocrine therapy resistance has been reported in young BC patients [9]. The incidence of de novo metastatic breast cancer (dnMBC) is approximately 2.6%, and the metastasis rate of primary early-stage or locally advanced BC is 27.1% in young patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…According to the American Cancer Society, there is a substantial increase in cancer rates, particularly in African regions (Jemal et al 2012;Shah et al 2013). Breast cancer is the most common cancer in women worldwide, accounting for 25% of cancer cases (Shah et al 2020).…”
Section: Introductionmentioning
confidence: 99%